Socialisation, Role theory, and Infrapolitics: Officers of the Irish Defence Forces and Civilian Higher Education since the 1960s - GIBSON, ANDREW GERARD (Trinity College Dublin. School of Education. Discipline of Education, 2020)
The military profession has a long history, and its institutions of education have been central to the development of military officers. Questions about the higher education of officers became increasingly important in the wake of World War 2 and the changing nature of military authority and the roles that military officers would be expected to fill. In Ireland these changes became manifest in the advent of the decision in 1969 to send Army officers to university in University College Galway. Combining documentary and archival research with data generated through semi-structured interviews with 46 retired and serving officers, it adopts a conceptual framework of role theory combined with ideas from James C. Scott in a case study approach to examine the origins and effects of the USAC scheme for the civilian higher education of Irish military officers since 1969. It answers the question of how officers in the Defence Forces interacted with civilian higher education at undergraduate level, and how this influenced their socialisation, professional formation, and the implications of higher education for them as individuals and for their military role.
APPROVED
Keywords: sociology of the military; Irish Defence Forces; higher education; sociology of education; military education; socialisation